Determining the main factors that influence for the tourist’s revisit intention in Melaka - Omar, Siti Nazriyanisofea; Saad, Mazni (2019)
Recent years, Melaka has become one of the hotspot attractions places where from the statistics show that tourist arrival in Melaka keeps increasing every year that generates income to the community in Melaka and the country. The quiet huge number of returning tourists in Melaka makes the researcher wants to investigate the main reason or factor that lead the tourists willing to return again. Thus, the purpose of this study is to examine the relationship between service provided, social media and cultural values impact be the factors that can influence them to have revisit intention Melaka. Data is collected from tourists that already revisit Melaka through survey form and total of respondents is 58. There are notable findings where there is a significant relationship between service provided, social media and cultural values impact and revisit intention. There have several limitations such as sample size and the data collection is small and sampling bias and margin of error.